2021
DOI: 10.1051/0004-6361/202039609
|View full text |Cite
|
Sign up to set email alerts
|

Seeds of Life in Space (SOLIS)

Abstract: Context. The isotopic ratio of nitrogen presents a wide range of values in the Solar System: from ~140 in meteorites and comets to 441 in the solar wind. In star-forming systems, we observe even a higher spread of ~150–1000. The origin of these differences is still unclear. Aims. Chemical reactions in the gas phase are one of the possible processes that could modify the 14N/15N ratio. We aim to investigate if and how the passage of a shock wave in the interstellar medium, which activates a rich chemistry, can … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 53 publications
(79 reference statements)
8
7
1
Order By: Relevance
“…Our column density determinations for HCN and HNC towards L1157-mm and L1157-B1 are in good agreement with those of Bachiller & Pérez-Gutiérrez (1997). Recently, Benedettini et al (2021) observed the H 13 CN and HC 15 N J=1-0 line emission at 4 ′′ resolution toward L1157-B1 using NOEMA, as part of the Large Program SOLIS. Their radiative transfer modelling of both lines yielded N (H 13 CN) ∼ 7 × 10 12 cm −2 and N (HC 15 N) ∼ 2 × 10 12 cm −2 .…”
Section: Line Excitationsupporting
confidence: 87%
See 4 more Smart Citations
“…Our column density determinations for HCN and HNC towards L1157-mm and L1157-B1 are in good agreement with those of Bachiller & Pérez-Gutiérrez (1997). Recently, Benedettini et al (2021) observed the H 13 CN and HC 15 N J=1-0 line emission at 4 ′′ resolution toward L1157-B1 using NOEMA, as part of the Large Program SOLIS. Their radiative transfer modelling of both lines yielded N (H 13 CN) ∼ 7 × 10 12 cm −2 and N (HC 15 N) ∼ 2 × 10 12 cm −2 .…”
Section: Line Excitationsupporting
confidence: 87%
“…Recently, Benedettini et al (2021) have investigated the 14 N/ 15 N fractionation of HCN in the two shocked clumps, B1 and B0, of the L1157 outflow using the NOEMA interferometer at ∼ 3 ′′ resolution, and obtained 14 N/ 15 N= 340 ± 70, in good agreement with our determination (see Table 4). Based on the chemical shock modelling, Benedettini et al (2021) conclude that the rich gas chemistry activated by the passage of the shock does not affect the 14 N/ 15 N ratio with respect to the local ISM value. This conclusion is observationally confirmed by our results.…”
Section: Nitrogensupporting
confidence: 87%
See 3 more Smart Citations